MENGAPA KOMPETENSI PEMERIKSAAN PRENATAL KONSELING TANDA BAHAYA OLEH BIDAN DI PUSKESMAS LEBIH BAIK DIBANDINGKAN PRAKTIK SWASTA DI INDONESIA? DATA INDONESIA FAMILY LIFE SURVEY (IFLS) 2007 - Helen Try Juni Asti; Ova Emilia; Mubasysyir Hasanbasri (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2016)
Background: Indonesia's maternal mortality rate increased in 2013 while antenatal care coverage K4 also increased. The element is important to know the health status of the pregnancy is highly dependent on the implementation of the prenatal examination by a midwife. Midwives have a good quality in the implementation of prenatal examinations can reduce morbidity and mortality of pregnant women.Objectives: To investigate implementation prenatal examination in Indonesia by midwives in the health center facilities (public) and private practice, working time, training participation, geographical location (urban-rural), and the regions lagging.Methods: This research is a quantitative research. We analyzed 1,433 midwives from 13 provinces in Indonesia which respondents IFLS 2007. The implementation details of prenatal care by midwives obtained from nine item prenatal procedures on questionnaires vignettes.Results: Statistical tests showed that the percentage of implementation of prenatal care is still low. Variable types of facilities most influence on the implementation of prenatal examinations and tests hemoglobin fe tablet. Public facilities tend to be carrying out the procedure with (OR 1,30; CI 1,04-1,61) and hemoglobin tests (OR 1,62; CI 1,30-2,02) compared to private practice. Variable training participation proved to be the most influential on the implementation of urine testing, counseling danger signs of pregnancy, and ask a history of high blood, midwife training are more likely to implementing procedures prenatal urine (OR 1,95; CI 1,21-3,14), counseling danger signs of pregnancy (OR 1,45; CI 0,98-2,15], and asking a history of high blood pressure (OR 1,61; CI 1,12-2,33) compared the midwife did not follow the training.still low. Strategies to increase implementation of antenatal care by improving the function of regulation, training and continuing education, and supervision.